Correlation of Meniscal Tear with Timing of Anterior Cruciate Ligament Reconstruction in Patients without Initially Concurrent Meniscal Tear - Chen, Kun-Hui; Chiang, En-Rung; Wang, Hsin-Yi; Ma, Hsiao-Li (The Journal of Knee Surgery, 2019)
The incidence of meniscal tear was reported to increase with the delay of anterior cruciate ligament reconstruction (ACLR). The tear may occur concurrently with the ACL injury or after the ACL injury. Few studies had focused on the patients whose meniscus is intact during ACL injury. We determined the correlation between timing of surgery and incidence of meniscal tears in ACL-deficient knees with initially intact meniscus. We retrospectively reviewed 387 patients who had undergone primary ACLR. Time of initial ACL injury, magnetic resonance imaging (MRI) examination, and surgery was recorded. The MRI was reviewed by experienced radiologic and orthopaedic doctors. Intraoperative arthroscopic images were also obtained and reviewed. The type of tear noted during surgery was classified according to the modification of International Society of Arthroscopy, Knee Surgery and Orthopaedic Sports Medicine classification of meniscal tears. Patients were divided into early (surgery within 12 months from injury) and late surgery group (surgery at more than 12 months from injury). There were 216 patients with intact medial meniscus and 257 patients with intact lateral meniscus on the postinjury MRI study. The incidence of medial meniscus tear (MMT) was significantly higher than lateral meniscus tear (LMT) during the ACLR (33.8 vs. 19.8%, p < 0.001). The incidence of MMT is higher in late group than in early group (53.7 vs. 29.1%, p = 0.004, odds ratio= 2.815). The incidence of LMT is mildly higher in late group but without statistics significance (23.8 vs. 18.6%, p = 0.364). In both MMT and LMT, the most common injury pattern observed was a longitudinal tear. The incidence of each type is not different between early and late group. For patients without concurrent meniscal injuries with the ACL tear, the incidence of MMT significantly increased if ACLR was performed more than 12 months after injury. The medial meniscus was more prone to injury than the lateral meniscus in chronic ACL-deficient knee. ACLR should be performed earlier to reduce the risk of meniscal tears for patients without initially concurrent meniscal tear.
Keywords: anterior cruciate ligament injuries; anterior cruciate ligament reconstructions; meniscus injuries